A greater goal : the epic battle for equal pay in women's soccer-and beyond - Rusch, Elizabeth (Greenwillow Books, An Imprint of HarperCollins Publishers, 2024)
"A history of the more than 250 women who have played for the U.S. National Soccer Team and their battle for equal pay"--